2015
DOI: 10.1097/mog.0000000000000144
|View full text |Cite
|
Sign up to set email alerts
|

Role of endoplasmic reticulum stress and autophagy as interlinking pathways in the pathogenesis of inflammatory bowel disease

Abstract: Purpose of review The purpose of this study is to provide an overview of the role of endoplasmic reticulum (ER) stress and the unfolded protein response (UPR) in inflammatory bowel disease (IBD). Recent findings Human genetic studies have identified several UPR-related genes and autophagy-related genes as IBD risk loci. Impairment of each branch of the UPR causes spontaneous enteritis or creates higher susceptibility for intestinal inflammation in model systems. Deficiency of either UPR or autophagy in small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 66 publications
(83 reference statements)
2
60
0
1
Order By: Relevance
“…The link between the IRE1α pathway of the UPR and NOD1/2 is of particular interest for CD, since this inflammatory pathology has been linked to ER stress-mediated dysfunction of Paneth cells (reviewed in [78, 79]). Interestingly, two proteins affected by CD-associated risk alleles, ATG16L1, required for autophagy, and XBP1, a regulator of the unfolded protein response, alleviate ER stress and reduce activation of the IRE1α pathway.…”
Section: Nod1/2 Sensing Of Endoplasmic Reticulum (Er) Stressmentioning
confidence: 99%
“…The link between the IRE1α pathway of the UPR and NOD1/2 is of particular interest for CD, since this inflammatory pathology has been linked to ER stress-mediated dysfunction of Paneth cells (reviewed in [78, 79]). Interestingly, two proteins affected by CD-associated risk alleles, ATG16L1, required for autophagy, and XBP1, a regulator of the unfolded protein response, alleviate ER stress and reduce activation of the IRE1α pathway.…”
Section: Nod1/2 Sensing Of Endoplasmic Reticulum (Er) Stressmentioning
confidence: 99%
“…This process can be promoted by autophagy (4547). Evidence has shown that impaired autophagy disturbs the function of intestinal epithelial cells and influences the innate and adaptive immune responses, ROS production, and endoplasmic reticulum (ER) stress, leading to abnormal inflammatory reaction, and ultimately promoting the occurrence and development of IBD (7, 4850). …”
Section: The Roles Of Autophagy In Ibdmentioning
confidence: 99%
“…Recent reports suggested that the macro-autophagy (hereafter autophagy) pathway, an evolutionarily conserved cellular protein degradation mechanism, contributes to ER stress [12, 13]. Autophagy is a catabolic process for autophagosome-lysosomal degradation of bulk cytoplasmic content of proteins.…”
Section: Introductionmentioning
confidence: 99%